International tooth removal in Neolithic Italian women - Robb, John
As many an excavator Ñ and many an older person Ñ knows, it is in the nature of human teeth to fall out, before death if they can, after and into the ground if they may not. So any consideration of tooth loss as we see it in prehistoric remains Ñ if it is to be the cultural evidence for the deliberate removal of teeth Ñ needs properly to identify a sufficiently distinctive pattern.